2012
DOI: 10.1016/j.cub.2012.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila TRPML Is Required for TORC1 Activation

Abstract: Summary Loss-of-function mutations in TRPML1 (Transient Receptor Potential Mucolipin 1) cause a lysosomal storage disorder called mucolipidosis type IV (MLIV). Previously, we established a Drosophila model for MLIV by knocking out the single TRPML1 homolog expressed in flies [1]. The mutant animals displayed impaired autophagy, and reduced viability during the pupal period—a phase when wild-type animals rely on autophagic sources for nutrients. However, the specific defect in autophagy has remained unclear. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(152 citation statements)
references
References 35 publications
11
136
1
Order By: Relevance
“…As predicted by theoretical calculations [35] and as shown by UV-vis spectroscopy here (see Figure 4 (c)), the C, W co-doped material had an absorbance significantly shifted towards the visible region. However, despite the enhanced optical properties of the W-doped and co-doped TiO 2 catalysts, these were considerably poorer photo-oxidation catalysts (see Figure 4(c)) compared to C-TiO 2 materials.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…As predicted by theoretical calculations [35] and as shown by UV-vis spectroscopy here (see Figure 4 (c)), the C, W co-doped material had an absorbance significantly shifted towards the visible region. However, despite the enhanced optical properties of the W-doped and co-doped TiO 2 catalysts, these were considerably poorer photo-oxidation catalysts (see Figure 4(c)) compared to C-TiO 2 materials.…”
Section: Resultssupporting
confidence: 60%
“…Codoping carbon and tungsten has been reported to yield such a passivation effect in comparison to singly doped tungsten or carbon TiO 2 . This reported passivation is due to the formation of a C 2p -W 5d hybridized band [35] when dopants are located near one other (as the nearest neighbour or the second nearest neighbour). This strengthens hybridization between C 2p and O 2p resulting in a fully occupied band of higher energy than the top of the valence band edge and at the same time forms a continuum-like band between the conduction band and tungsten dopant d states below.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, nutrient-sensitive regulation of ML1 channels may link lysosome function with nutrient availability via mTORC1, PI(3,5)P 2 , and TFEB. Although our study has focused on the effect of mTORC1 inhibition on up-regulation of TRPML1, it has recently been demonstrated that the Drosophila homolog of TRPML1, TRPML, regulates the activity of TORC1 in vivo (43). Hence, TRPML1 and TORC1 may constitute a feedback loop to regulate amino acid homeostasis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Bafilomycin A1 (Baf. A1)-a cell-permeant inhibitor of the vacuolar-type H þ -ATPase, results in loss of the lysosomal/late endosomal proton gradient and eventually leads to the depletion of luminal calcium 34 . By using Baf.…”
Section: Articlementioning
confidence: 99%